Transient analysis of short circuit faults in hybrid networks - Zangina *†, J.S.; Suleiman‡, M.A.; Ahmed, A. (International Journal of Mathematical Analysis and Modelling, 2024)
Hybrid power systems, integrating renewable energy sources, energy storage devices, and conventional generators, are at the vanguard of the transition towards sustainable energy solutions. However, ensuring the robustness and reliability of these systems under fault conditions, particularly short circuit faults, remains a challenge. This research explores the complexity of hybrid networks, conducting a comprehensive transient analysis of short-circuit faults to enhance the understanding of their impact. The study employs advanced simulation techniques and state-of-the-art modeling approaches to examine the dynamic behavior of hybrid networks during fault events. Through detailed investigations, this research aims to unravel the transient responses of various fault locations, including fault resistance, and transmission line length, renewable energy sources, when subjected to short circuit faults. The findings of this study not only contribute to the academic discourse surrounding hybrid power systems but also provide invaluable insights for industry practitioners, guiding the development of reliable and efficient hybrid energy infrastructures for a sustainable future.